1994
DOI: 10.1016/1044-0305(94)80002-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of protonation site on bond strengths in simple peptides: Application of Ab initio and modified neglect of differential overlap bond orders and modified neglect of differential overlap energy partitioning

Abstract: A comparative study of ab initio 6-31G(*) and semiempirical modified neglect of differential overlap (MNDO) bond orders and MNDO diatomic energy contributions for the description of bond strengths in neutral and protonated glycine, diglycine, triglycine, and dialanine is presented. Good correlations were found between 6-31G(*) and MNDO bond orders and between MNDO bond orders and diatomic energy contributions. Although bond orders and diatomic energy contributions are inherently different quantities, both pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 40 publications
2
72
0
Order By: Relevance
“…First, relatively simple bond order calculations clearly indicated that the amide bond order (or, somewhat imprecisely, the amide bond strength) was much lower (weaker) in amide-N-protonated forms than in amide-O-protonated forms [12,20]. These calculations also implied that even though the amide-O-protonated forms are more stable energetically, they do not necessarily (or exclusively) trigger amide bond fragmentation.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…First, relatively simple bond order calculations clearly indicated that the amide bond order (or, somewhat imprecisely, the amide bond strength) was much lower (weaker) in amide-N-protonated forms than in amide-O-protonated forms [12,20]. These calculations also implied that even though the amide-O-protonated forms are more stable energetically, they do not necessarily (or exclusively) trigger amide bond fragmentation.…”
mentioning
confidence: 87%
“…Besides experimental studies, theoretical (quantum chemical) calculations have also played a role in the development of the mobile proton model [12,20,21]. First, relatively simple bond order calculations clearly indicated that the amide bond order (or, somewhat imprecisely, the amide bond strength) was much lower (weaker) in amide-N-protonated forms than in amide-O-protonated forms [12,20].…”
mentioning
confidence: 99%
“…Because this thermal process is caused by vibrational activation of closed valence shell ions, the fragmentation mechanism can be explained by the "mobile proton" model [34]. These fragments are the result of the cleavage of the CO-NH bond that is weakened by the protonation of the nitrogen of the amide group [35,36]. The CID-like fragments (a-, b-, and y-type) can then be favored by the acidity of the matrix.…”
Section: Influence Of the Matrixmentioning
confidence: 99%
“…T hough it is not the only factor, it is well established [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] that proton migration is crucial in inducing fragmentation in tandem mass spectrometry (MS/MS) experiments. The ease or difficulty of proton migration depends on the proton affinity (PA) [or the related gas-phase basicity (GB)] values of the protonation sites.…”
Section: Introductionmentioning
confidence: 99%